The Influence of the Quantity and Quality of Education on Black-White Earnings Differentials: Some New Evidence - Link, Charles R.; Ratledge, Edward C. (The Review of Economics and Statistics, 1975)
Charles R. Link, Edward C. Ratledge, The Influence of the Quantity and Quality of Education on Black-White Earnings Differentials: Some New Evidence, The Review of Economics and Statistics, Vol. 57, No. 3 (Aug., 1975), pp. 346-350